2005
DOI: 10.1186/1476-8518-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic arthritis: Pathogenesis and novel immunomodulatory approaches to treatment

Abstract: Psoriatic arthritis (PsA) is a chronic inflammatory arthropathy characterized by the association of arthritis and psoriasis. PsA runs a variable course, from mild synovitis to severe, progressive, erosive arthropathy. The pathogenesis of PsA involves alteration in the components of the immune response, although the exact cause of PsA is unknown. A number of patients with severe peripheral arthritis fail to respond to standard conventional therapy. Advances in biotechnology and in our understanding of the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 57 publications
1
0
0
Order By: Relevance
“…Accordingly, this study revealed a number of dysregulated chemokines and their receptors in the development of AMA, such as Adam8 , Saa3 , Il1rn , Ccl2 , Ccl7 , Ccl9 , Ccr2 , and Cxcl1 . GO enrichment analysis revealed that immune response and inflammatory response were significantly enriched biological processes of DEGs, which were linked to RA and in line with previous studies [ 2 4 , 27 ]. Those biological processes-associated genes, such as Cxcl1 , Ccl2 , Ccr2 , Fcgr1 , and Ccl7 were also associated with molecular functions of chemokine activity, chemokine receptor binding, and cytokine activity.…”
Section: Discussionsupporting
confidence: 90%
“…Accordingly, this study revealed a number of dysregulated chemokines and their receptors in the development of AMA, such as Adam8 , Saa3 , Il1rn , Ccl2 , Ccl7 , Ccl9 , Ccr2 , and Cxcl1 . GO enrichment analysis revealed that immune response and inflammatory response were significantly enriched biological processes of DEGs, which were linked to RA and in line with previous studies [ 2 4 , 27 ]. Those biological processes-associated genes, such as Cxcl1 , Ccl2 , Ccr2 , Fcgr1 , and Ccl7 were also associated with molecular functions of chemokine activity, chemokine receptor binding, and cytokine activity.…”
Section: Discussionsupporting
confidence: 90%
“…These improvements encompass not only the primary signs and symptoms of arthritis but also extend to dactylitis and enthesitis, as well as skin manifestations. Furthermore, there have been enhancements in functional status and quality of life, along with a notable reduction in the progression of radiographic damage [106]. While combination therapy has been shown to be very effective for plaque psoriasis, with promising combinations of pioglitazone, the overall approach remains complicated and complex, especially for patients with serious comorbidities [107,108].…”
Section: Discussionmentioning
confidence: 99%